2013
DOI: 10.1007/s10565-013-9251-4
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin induces apoptosis by suppressing E6 and E7 expressions and activating intrinsic signaling pathways in HPV-16 cervical cancer cells

Abstract: Wogonin is a flavonoid compound extracted from Scutellaria baicalensis and is well known as a benzodiazepine receptor ligand with anxiolytic effects. Many recent studies have demonstrated that wogonin modulates angiogenesis, proliferation, invasion, and tumor progress in various cancer tissues. We further explored the mechanism of action of wogonin on cervical cancer cells that contain or lack human papillomavirus (HPV) DNA. Wogonin was cytotoxic to HPV 16 (+) cervical cancer cells, SiHa and CaSki, but not to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In intrinsic pathway or mitochondrial pathway, the balance between Bcl-2 family members such as Bcl-xL and Bax is important while in extrinsic apoptosis pathway Fas and FasL are the key inducers. In both the pathways cleavage of caspases and PARP plays a crucial role (20,21). Fig.…”
Section: Influence Of Bfs On the Regulators Involved In Intrinsic Apomentioning
confidence: 99%
“…In intrinsic pathway or mitochondrial pathway, the balance between Bcl-2 family members such as Bcl-xL and Bax is important while in extrinsic apoptosis pathway Fas and FasL are the key inducers. In both the pathways cleavage of caspases and PARP plays a crucial role (20,21). Fig.…”
Section: Influence Of Bfs On the Regulators Involved In Intrinsic Apomentioning
confidence: 99%
“…EET treatment resulted in mitochondrial membrane potential collapse and the release of cytochrome c Mitochondrial dysfunction has been reported to play a vital role in intrinsic apoptosis processes, which is characterized by the collapse of transmembrane potential [12]. In view of the increase in levels of activated caspase-3 and caspase-9 that was observed in HepG 2 cells exposed to EET, we then evaluated whether treatment with EET induced a loss in mitochondria transmembrane potential (⊿ψm) and the release of cytochrome c from mitochondria as proof of mitochondriamediated apoptosis.…”
Section: Eet Regulated the Expression Of Apoptosis-related Protein Inmentioning
confidence: 99%
“…E6 and E7 oncogenes have been found to induce the epithelialto-mesenchymal transition (EMT), a process required for the tumor cells to invade into the bloodstream and metastasize at other place in the body. Using the epithelial MDCK cell line as an in vitro model, the study by Kim et al (2013) showed that ectopic expression of E6/E7 can induce cobblestone-shaped epithelial cell formation from spindle-shaped mesenchymal cells. Moreover, they also showed that E6 and E7 could activate the EMT-inducing transcriptional factors such as Slug, Twist, ZEB1, and ZEB2 followed by an increase in the migratory and invasive potentials of the cells.…”
Section: Activation Of Invasion and Metastasismentioning
confidence: 99%